Gas-Phase Hydrogenation of Furfural to Furfuryl Alcohol over Cu-ZnO-Al2O3 Catalysts Prepared from Layered Double Hydroxides - Bertolini, Guillermo R.; Jiménez-Gómez, Carmen Pilar; Cecilia-Buenestado, Juan Antonio; Maireles-Torres, Pedro Jesús (MDPI, 2020)
Several layered double hydroxides (LDHs) with general chemical composition (Cu,Zn)1-xAlx(OH)2(CO3)x/2 .. mH2O have been synthesized by the co-precipitation method, maintaining a (M2+/M3+) molar ratio of 3, and varying the Cu2+/Zn2+ molar ratio between 0.2 and 6.0. After calcination and reduction steps, Cu/ZnO/Al2O3 catalysts were synthesized. These catalysts were characterized by X-ray diffraction (XRD), transmission electron microscopy (TEM), H2 thermoprogrammed reduction (H2-TPR), N2 adsorption-desorption at -196 ºC, N2O titration, X-ray photoelectron miscroscopy (XPS), NH3-thermoprogramed desorption (NH3-TPD) and CO2- thermoprogrammed desorption (CO2-TPD). The characterization data revealed that these catalysts are mainly meso-and macroporous, where Cu, ZnO and Al2O3 are well dispersed. The catalytic results show that these catalysts are active in the gas-phase hydrogenation of furfural, being highly selective to furfuryl alcohol (FOL) and reaching the highest FOL yield for the catalyst with a Cu2+/Zn2+ molar ratio of 1. In an additional study, the influence of the aging time on the synthesis of the LDHs was also evaluated. The catalytic data revealed that the use of shorter aging time in the formation of the LDH has a beneficial effect on the catalytic behavior, since more disordered structures with a higher amount of available Cu sites is obtained, leading to a higher yield towards FOL (71% after 5 h of time-on-stream at 210 ºC).
Keywords: Hidróxidos dobles laminares; Catalizadores metálicos; Aldehidos; layered double hydroxides; Copper-based catalysts; Cu/ZnO/Al2O3; furfural; furfuryl alcohol; biorefinery; biomass valorization